The relation between obstetric conjugate diameter during pregnancy and the type of delivery: a narrative review - Satte, Mahmoud S. (International Journal of Research in Medical Sciences, 2023)
Obstetric conjugate diameter is the first point of the maternal pelvis through which the head of the fetus has to pass during the stages of birth and it is the most important female pelvimetry during pregnancy. This review aims to find out the relation between obstetric conjugate diameter measured by radiography during pregnancy and the type of birth, vaginally, or by caesarean. Narrative review conducted at Najran Medicine College (Kingdom of Saudi Arabia). METHODS: Articles review describing the association between obstetric conjugate diameters measured by radiography during the last stage of pregnancy and type of delivery were selected from the electronic database (PubMed, LILACS, SciELO, and Google scholar). The search date was on January to February 2023. This review showed that there is a relationship between obstetric conjugate diameter and the type of delivery and can be used in predicting the mode of birth (vaginal or cesarean). This knowledge is important for obstetricians and gynecologists to predict the type of childbirth, vaginally, or by cesarean.